A common functional observer scheme for three systems with unknown inputs. Issue 10 (July 2016) - Ng, Jiunn Yea; Tan, Chee Pin; Trinh, Hieu; Ng, Kok Yew
Abstract: This paper presents a novel common functional observer scheme for three systems with unknown inputs. The scheme uses three observers in cascade with two logic switches. The existence conditions of the scheme are investigated and presented in terms of the original system matrices. Significantly, the conditions allow the observers to be designed independently of each other which greatly simplify the design process, and also serve as a basis of comparison for future development of common functional observer schemes. A numerical example is given to illustrate the effectiveness of the proposed scheme.